2021
DOI: 10.1259/bjr.20201215
|View full text |Cite
|
Sign up to set email alerts
|

Clinical quantitative MRI and the need for metrology

Abstract: MRI has been an essential diagnostic tool in healthcare for several decades. It offers unique insights into most tissues without the need for ionising radiation. Historically, MRI has been predominantly used qualitatively, images are formed to allow visual discrimination of tissues types and pathologies, rather than providing quantitative measurements. Increasingly, quantitative MRI (qMRI) is also finding clinical application, where images provide the basis for physical measurements of, e.g. tissue volume meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…To perform a gap analysis, we must provide a standard from which to assess the gap. That standard is established in metrology [60,106,107]. Box 2 gives an overview of metrology in relation to qMR IBs and Table 2 provides a gap analysis of relevant quality management domains and encapsulates the findings of this study with suggested best practice, the gaps and the challenges we face to bridge those gaps.…”
Section: Gap Analysis Of Qmr Validation and Quality Managementmentioning
confidence: 99%
“…To perform a gap analysis, we must provide a standard from which to assess the gap. That standard is established in metrology [60,106,107]. Box 2 gives an overview of metrology in relation to qMR IBs and Table 2 provides a gap analysis of relevant quality management domains and encapsulates the findings of this study with suggested best practice, the gaps and the challenges we face to bridge those gaps.…”
Section: Gap Analysis Of Qmr Validation and Quality Managementmentioning
confidence: 99%
“…In order to make the result of a quantitative MRI technique a proper measurement result in the strict sense, the uncertainty with which the property values have been estimated must be assessed [ 41 ]. Up to now, only a few works have dealt with uncertainty quantification in EPT and only in theoretical cases [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, conventional MRI sequences can only assess the macroscopic morphological features of lesions, which makes it challenging to effectively evaluate features involving cellular microscopic information, such as Ki-67. Compared with conventional MRI, quantitative MRI can accurately assess the microscopic information of tissues, and with the continued progress in related technologies, an increasing number of studies have emphasized the growing contribution of quantitative MRI as a source of quantitative biomarkers (7,8). Intravoxel incoherent motion (IVIM) is a promising quantitative MRI sequence in which the biexponential model can reflect the true diffusion information and microcirculatory perfusion of water molecules in tissues, whereas the stretched exponential model describes the average diffusion information of water molecules and structural complexity in tissues (9,10).…”
Section: Introductionmentioning
confidence: 99%